Nitrate, sodium and macronutrients in transition foods for infants and young children of the Artiype baby food of vegetables with meats - Garcia, Lorena Natalino Haber [UNESP]; Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Castro, Bruna Godoi [UNESP]; Velame, Marise Santiago [UNESP]; Santos, Amanda de Oliveira [UNESP]; Caron, Evelyn Fernanda Flores [UNESP]; Cerqueira-Cezar, Camila Koutsodontis [UNESP]; Baldini, Eduardo Delbon [UNESP]; Possebon, Fabio Sossai [UNESP]; Pereira, Juliano Goncalves [UNESP]; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2024)
Transitional foods for infants and children of early childhood, also popularly known as baby-food, are used in order to complement the diet, gradually introducing new sources of nutrients to children in the weaning phase. The objective is to evaluate the chemical and biochemical quality of transitional foods for infants and young children such as vegetable and meat baby-food (VMBF) and vegetable and chicken baby-food (VCBF). 20 samples of VMBF and VCBF were analyzed. The levels of nitrate, sodium, pH, macronutrients (protein, lipid and carbohydrate), total caloric value (TCV), humidity, fixed mineral residue (FMR) and solid matter (SM) were determined in duplicate. The results showed that the two types of baby-food (VMBF and VCBF) did not show statistical differences (p > 0.05). Regarding the current legislation, it was found that 100% of the samples of VMBF and VCBF presented within the reference values for the pH and SM tests. The VMBF samples showed percentages of 25%, 100%, 25% and 25% for the nitrate, sodium, protein and TCV assays that were outside the permitted values, respectively. The samples of VCBF, however, presented percentage indexes of 40%, 80% and 40% for the tests of nitrate, sodium and protein outside the established reference standards, respectively. It is concluded that the high levels of nitrate and sodium are worrisome, being necessary the active inspection by Organs regulating agencies in relation to these foods due to its importance in child development.
Keywords: Macronutrients; Sodium; Baby-food